The Role of an Interactive Visual Learning Tool and Its Personalizability in Online Learning: Flow Experience - Ha, Young; Im, Hyunjoo (Online Learning, 2020)
The purpose of this study was to examine the effect of interactive online learning tools on college student learning using flow as the guiding perspective. Study 1 was conducted to test the effect of online interactivity manipulated by dynamic visual learning tools on student’s flow experience, level of telepresence, actual performance in test, and perceived values of such activities. Study 2 was designed to test the effect of personalizability of difficulty levels in the interactive online activity on students’ learning experience. The results found that interactive online learning tools can facilitate student’s active learning process by increasing attention, curiosity, and interest about the online activity, and by reducing awareness of physical surroundings. In addition, the interactive activity significantly improved students’ test scores. This study also found that personalized difficulty options available in the interactive online activity significantly increased students’ perceived hedonic value (i.e., enjoyment) of and the level of satisfaction with the activity. The results emphasize the critical role of interactive visual learning tool in the online activities in improving students’ flow experience and actual performance. Personalizability of task levels is also recommended to be used in online activities to increase students’ perceived hedonic value and satisfaction with such online activities.